Agriculture Production Cooperatives in This Country– Social Functions and Competitiveness - Rakadjiiska, Temenuga (Research Papers, 2006)
The main theses of this article – the contemporary agriculture production cooperatives as a structure of the civil society in Bulgaria does not meet it’s social functions especially at the village and in this way to improve all the village life. The big part of managers, are representatives of the old style of the management and have not had a new managerial culture and market’s orientation. Their expectations are to the equal budget’s subsidies without taking into account the real results and social programs.In Bulgaria the extent of impersonal trust is lower and the extent of the economic action’s embeddedness into the social relations is high. For this reason is very difficult to construct the adequate criteria for selective subsidizing but this is very important for improving it’s economic results and it’s opportunity to realize their social functions.